(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2012)
Caesalpinia sappan Linn., a traditional Indian medicinal plant used widely in oriental medicine. The plant extracts were found to be a good source of secondary metabolites, vitamins and metals. The extracts were further tested against certain human pathogenic microbes. The methanol and ethyl acetate extracts of the heartwood was found to be effective against certain pathogenic microbes. Key words: Caesalpinia sappan; Secondary metabolites; Vitamins; Antimicrobial activity DOI: http://dx.doi.org/10.3329/bjsir.v46i4.9586 BJSIR 2011; 46(4): 429-436